ABSCISIC ACID MEDIATED BIOCHEMICAL CHANGES IN SUNFLOWER (HELIANTHUS ANNUUS L.) GROWN UNDER DROUGHT AND WELL-WATERED FIELD CONDITIONS - S. Hussaina; M. F. Saleemb; J. Iqbala; M. Ibrahima; M. Ahmadd; S. M. Nadeeme; A. Alic; S. Attaa (Journal of Animal and Plant Sciences, 2015)
Water stress is a major and ever-present threat to crop production, especially where irrigation is an inevitable aid to agriculture. Three sunflower hybrids viz. DK-4040, S-278 and SF-187 were subjected to different irrigation regimes and ABA applications. Four irrigations applied at different times with and without ABA. In control treatment i.e. four irrigations were applied 25 days after sowing (DAS), at bud initiation, flower initiation and achene formation with no ABA spray. In drought stress treatment three irrigations were applied and one irrigation skipped either at bud or at flower initiation stage with and without ABA application. The experiment laid out in RCBD with factorial arrangements of treatments. LSD test was employed to compare the means of treatment at 5% level of probability. Drought significantly decreased achene yield and oil content but increased achene protein content and leaf compatible solutes in sunflower but vice versa happened by application of ABA. Drought stress to sunflower hybrids at bud or at flower initiation increased stearic and oleic acid and decreased palmitic and linoleic acid while exogenous application of ABA under water deficit at both stages slightly decreased stearic and oleic acid but increased palmitic and linoleic acid. Sunflower crop under water deficits conditions can be grown by application of ABA which is helpful in improving the drought tolerance as well as quality of oil.
Keywords: Sunflower; Abscisic acid; Drought tolerance; Compatible solutes; Fatty acids